2013
DOI: 10.1093/gerona/glt169
|View full text |Cite
|
Sign up to set email alerts
|

Liver Aging and Pseudocapillarization in a Werner Syndrome Mouse Model

Abstract: Werner syndrome is a progeric syndrome characterized by premature atherosclerosis, diabetes, cancer, and death in humans. The knockout mouse model created by deletion of the RecQ helicase domain of the mouse Wrn homologue gene (Wrn(∆hel/∆hel)) is of great interest because it develops atherosclerosis and hypertriglyceridemia, conditions associated with aging liver and sinusoidal changes. Here, we show that Wrn(∆hel/∆hel) mice exhibit increased extracellular matrix, defenestration, decreased fenestration diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 48 publications
6
39
0
Order By: Relevance
“…In regard to mitochondria, it has been reported that aging results in increased mitochondrial size (see Le Couteur et al, 2010) and in some cases this increase can be accompanied by modification of cristal morphology (Sastre et al, 1996). These changes have been confirmed in mice with different progeroid syndromes (Cogger et al, 2013; Gregg et al, 2012) strengthening the idea of increased mitochondrial size during aging.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In regard to mitochondria, it has been reported that aging results in increased mitochondrial size (see Le Couteur et al, 2010) and in some cases this increase can be accompanied by modification of cristal morphology (Sastre et al, 1996). These changes have been confirmed in mice with different progeroid syndromes (Cogger et al, 2013; Gregg et al, 2012) strengthening the idea of increased mitochondrial size during aging.…”
Section: Discussionmentioning
confidence: 53%
“…that have implications for many diseases (Cogger et al, 2013; Gregg et al, 2012; Le Couteur et al, 2010). However, in this work we have only considered hepatocytes showing a typical morphology similar to that described in the literature (see for example, Pieri et al, 1980; Schmucker, 1990) and possible modifications on cell types other than hepatocytes have not been analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated B cells, DC, and Mf for transcription studies were cultured for 4 h in complete RPMI (RPMI 1640 with 10% FCS, 2 mM GlutaMAX, 100 U/ml penicillin, 100 mg/ml streptomycin, 1 mM sodium pyruvate, 10 mM HEPES, and 50 mM 2-ME from Thermo Fisher) with 1 mg/ml LPS (Escherichia coli K12, InvivoGen), and T cells with a 1:1 ratio of mouse T-Activator CD3/28 Dynabeads (Thermo Fisher). To isolate hepatocytes, LSEC, and KC for transcriptional analysis, livers of WT or KO mice were perfused with collagenase III and extracted as previously described (16,17). The resulting liver cell suspension was twice centrifuged at 54 3 g to pellet hepatocytes, and the residual supernatant was layered on a two-step Percoll gradient (25-50%) …”
Section: Mouse Immune Cell Purification and Stimulationmentioning
confidence: 99%
“…Hepatic sinusoidal fenestrations were measured in perfused livers by scanning electron microscopy as recently described (31).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%